Wrongful deaths : selected inquest records from nineteenth-century Korea - Kim, Sun Joo, 1962- (Korean studies of the Henry M. Jackson School of International Studies, 2014)
"This collection presents and analyzes inquest records that tell the stories of ordinary Korean people under the Chosŏn court (1392-1910). Extending the study of this period, usually limited to elites, into the realm of everyday life, each inquest record includes a detailed postmortem examination and features testimony from everyone directly or indirectly related to the incident. The result is an amazingly vivid, colloquial account of the vibrant, multifaceted societal and legal cultures of early modern Korea. Sun Joo Kim is the Harvard-Yenching Professor of Korean History at Harvard University. Jungwon Kim is assistant professor of Korean history at Columbia University; 'This book provides an extremely rare view into social interactions among people of quite different classes in Chosŏn Korea. Points of interest abound'--Robert E. Hegel, Washington University, St. Louis; 'This is an important contribution that significantly advances our knowledge of nineteenth-century Korean legal history. The translated cases shine by being able to introduce daily struggles of non-elites and illustrate the complex dynamics of the judiciary system during the last century of the Chosŏn dynasty'--Jisoo Kim, George Washington University"--